2020
DOI: 10.3390/rs12132110
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Index Estimation Algorithm for GF-5 Hyperspectral Data Based on Different Feature Selection and Machine Learning Methods

Abstract: Leaf area index (LAI) is an essential vegetation parameter that represents the light energy utilization and vegetation canopy structure. As the only in-operation hyperspectral satellite launched by China, GF-5 is potentially useful for accurate LAI estimation. However, there is no research focus on evaluating GF-5 data for LAI estimation. Hyperspectral remote sensing data contains abundant information about the reflective characteristics of vegetation canopies, but these abound data also easily result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…In aforementioned studies, the extracted spectral parameters and ML algorithms are combined to construct inversion models of physiological parameters. In recent years, algorithms for spectral features extraction such as principal component analysis (PCA), variable projection importance (VIP), genetic algorithm (GA), and continuous projection algorithm (SPA) have been widely used in studies of ground monitoring or satellite remote sensing [ 21 , 22 ]. These algorithms can effectively remove the redundancy in hyperspectral data, thus reduce the risk of overfitting, and finally obtained a model of robust and high prediction accuracy [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In aforementioned studies, the extracted spectral parameters and ML algorithms are combined to construct inversion models of physiological parameters. In recent years, algorithms for spectral features extraction such as principal component analysis (PCA), variable projection importance (VIP), genetic algorithm (GA), and continuous projection algorithm (SPA) have been widely used in studies of ground monitoring or satellite remote sensing [ 21 , 22 ]. These algorithms can effectively remove the redundancy in hyperspectral data, thus reduce the risk of overfitting, and finally obtained a model of robust and high prediction accuracy [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on LAI estimation also reported that using the same machine learning algorithm for both feature selection and regression was not always the optimal solution. It is interesting to note that Chen et al found the VSURF-RFR model to be the best, although in this case, the study object and the method of comparison were different [38]. Overall, our experiment indicates that using the same machine learning algorithm for feature selection and regression does not improve AGB estimation accuracy.…”
Section: Discussionmentioning
confidence: 59%
“…Machine learning algorithms such as RF have their own built-in feature selection functions that can be used for simultaneous feature selection and regression [38]. However, there is little evidence to indicate that a greater accuracy of AGB estimation is achieved when feature selection and regression are performed with the same algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the high potential of using spectral reflectance to estimate and classify the yield ( Yoosefzadeh-Najafabadi et al, 2021a ), leaf area index ( Chen et al, 2020 ), plant stress ( Feng et al, 2020 ), and carbon and nitrogen contents ( Omidi et al, 2020 ). In a study done by Zhang et al (2019) , significant association of red and NIR regions with yield are reported.…”
Section: Introductionmentioning
confidence: 99%